A systems approach to dynamic performance assessment in new food product development. (September 2019) - Horvat, Andrijana; Behdani, Behzad; Fogliano, Vincenzo; Luning, Pieternel A.
Abstract: Background: Despite a great deal of research and knowledge, the failure rate of new food products is still high. Developing new food products is complex, since multiple functions, i.e., marketing, technology, and consumer researchers, are involved. How their decisions interrelate and affect product performance over time, i.e., throughout product life-cycle, has been scarcely studied for the food domain. Systematic assessment of product performance factors can lead to improvement, but such approach is yet lacking for new food products. Scope and approach: The study aimed at understanding which factors are relevant to assess performance of new food products during its life-cycle. An integrated framework for performance assessment of a new food product was developed by performing a structured literature review and by using systems approach principles to synthesize the review findings. Key findings and conclusions: The integrated framework represents the three main functions in food NPD – consumer research, technology and marketing, and consists of 46 variables relevant for managing food performance during its life cycle. Seven reinforcing and four balancing feedback loops were identified, which provide insight in the causal relations between variables. The integrated framework provides understanding of how each of the functions contributes to the food product's overall performance, and how they can anticipate consequences of numerous changes throughout product's life on the overall product's success, e.g., sales. This system representation helps decision-makers to get insight into behaviour of the whole system and to leverage the performance of new food products. Highlights: Structured approach for developing an integrated food product performance framework. Systems approach is applicable for studying a complex dynamic problem such as food success. Means-criteria diagrams capture the complex nature of new food product performance. Feedback loops facilitate qualitative representation of behaviour over time. The integrated framework aims at facilitating improved NPD decision-making.